UJI KONFIRMASI DAN PENETAPAN KADAR MORFIN DENGAN KLT-SPEKTROFOTODENSITOMETRI - Wirasuta, I Made Agus Gelgel; Primaningrum, Ida Ayu Shanti; Astuti, Ketut Widyani (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 4 (2014): Indonesian Journal of Legal and Forensic Sciences, 2014)
Screening and determination test of morphine using TLC-Spectrophotodensitometry method have been studied. Screening test based on the hRfc – value and the correlation value between detected spectrum and reference. The analysis results were improved by using the shift of spectrum reaction. The maximal result of screening test was obtained when determinate the hRfc-value with error window of three and the spectrum correlation above 0.90. The reaction of spectrum shift showed that morphine spectrum was not significantly changed after plates sprayed with HCL 10% and KOH 0.1 M so that could be used to increasing the analysis result of substance identity determination. Validation of method showed precision of method was 1.69%, the limit of detection 93.1 ng/spot and the limit of quantitation was 310,3 ng, percentage recovery of morphine from plasma was 106.34 ng ±10.79 (10.1%). TLC Spectrophotodensitometry could be used as simple and cheap method for screening and determination test of the morphine.
Keywords: screening, determination, morphine, Al-TLC, spectrophotodensitometry